The Influence of Activity Based Costing System on Improving Performance: Examining the Modifying Role of Modify Balance Scorecard at Sudanese Banks (The International Journal for Scientific Research, 2026)
The study aimed to investigate the influence of Activity Based Costing Style on Improving Performance: Examining the modifying role of Modify Balance Scorecard at Sudanese Banks. The problem of the study focuses on a decrease of Improving Performance level at Sudanese Banks because of unawareness of implementing modern Managerial Accounting Styles. Three hypotheses were developed and a questionnaire was designed. After data collection and analysis from the respondents, the study reached up to modifying Modify Balance Scorecard relationship between Activity Based Costing style and Improving Performance with a change in the determination coefficients of (0.132). The study recommended there is a need to increase leadership & employees awareness in the importance of Activity Based Costing style, Modify Balance Scorecard & Improving Performance.
Keywords: Modify Balance Scorecard; Activity Based Costing Style; Improving Performance; Sudanese Banks